IMPLEMENTASI INSENTIF PAJAK UMKM DI ERA COVID-19 DI KECAMATAN GEDANGAN KABUPATEN SIDOARJO - Alfi Huurin Iin; Septrian Jihan Aulia Fistabella; Adellia Nanda Savira; Kalvin Edo Wahyudi (Universitas Halu Oleo, 2021)
It is known that the people's economy has experienced a significant decline due to the Covid -19 Pandemic which has spread in various regions in Indonesia. From an economic point of view, we found that there was a decrease in income felt by UMKM actors, one of which was in the Gedangan Sub-District, Sidoarjo District which was caused by the Covid-19 pandemic. So that we are interested in examining how the efforts made by the Government through the Ministry of Finance regarding Final Income Tax Incentives to deal with the decline in income faced by UMKM’s. This study aims to determine how the implementation of the Final PPh Tax Incentive policy for UMKM’s during the current Covid-19 pandemic and to find out how the impact felt by UMKM’s regarding the Final Income Tax incentives issued by the Indonesian Minister of Finance. The method we use in this research is descriptive qualitative with data collection techniques using interviews and observations. The results of this study indicate that the tax incentive policy can not be felt by UMKM actors in Gedangan District, this is due to the lack of socialization provided, resulting in their lack of knowledge about this policy and what conditions they must have to get tax incentives issued by the Ministry of Finance.